Prinsip Dasar dan Pengembangan Toleransi Intern dan Ektern Umat Beragama Perspektif Al-Qur’an - Wafa, Zamroni (Ad-DA'WAH, 2024)
Moderate Islamic da'wah has become an increasingly relevant topic in the political and social context in Indonesia. This da'wah emphasizes the values ​​of simplicity, tolerance, interfaith dialogue, and acceptance of differences. However, political realities in Indonesia are often complex and do not always support moderate da'wah efforts. This research explores the relationship between moderate Islamic da'wah and political realities in Indonesia, with a focus on the challenges and opportunities faced by moderate Islamic da'wah movements in facing diverse political dynamics. The aim of this research is to determine the extent of the role of moderate Islamic preaching in influencing societal harmony in political reality in Indonesia. This article concludes that although political realities in Indonesia are often challenging, moderate Islamic da'wah movements still have the opportunity to develop and make a positive contribution in building an inclusive and harmonious society. Collaborative efforts between various parties, including political elites, religious leaders, and civil society activists, are urgently needed to overcome challenges and strengthen the propagation of moderate Islam in Indonesia.